Dry Reforming of Methane on a Highly‐Active Ni‐CeO2 Catalyst: Effects of Metal‐Support Interactions on C−H Bond Breaking. (4th May 2016) - Liu, Zongyuan; Grinter, David C.; Lustemberg, Pablo G.; Nguyen‐Phan, Thuy‐Duong; Zhou, Yinghui; Luo, Si; Waluyo, Iradwikanari; Crumlin, Ethan J.; Stacchiola, Dario J.; Zhou, Jing; Carrasco, Javier; Busnengo, H. Fabio; et al.
Abstract: Ni‐CeO2 is a highly efficient, stable and non‐expensive catalyst for methane dry reforming at relative low temperatures (700 K). The active phase of the catalyst consists of small nanoparticles of nickel dispersed on partially reduced ceria. Experiments of ambient pressure XPS indicate that methane dissociates on Ni/CeO2 at temperatures as low as 300 K, generating CH x and CO x species on the surface of the catalyst. Strong metal–support interactions activate Ni for the dissociation of methane. The results of density‐functional calculations show a drop in the effective barrier for methane activation from 0.9 eV on Ni(111) to only 0.15 eV on Ni/CeO2− x (111). At 700 K, under methane dry reforming conditions, no signals for adsorbed CH x or C species are detected in the C 1s XPS region. The reforming of methane proceeds in a clean and efficient way.